ChemInform Abstract: Diastereo‐ and Enantioselective Synthesis of 1, 3, 5, 7‐Tetraol Structural Units Using a Prins Cyclization—Reductive Cleavage Sequence. Issue 31 (5th August 2014) - Brun, Elodie; Bellosta, Veronique; Cossy, Janine
Abstract The new method presented here provides access to all the possible diastereomers.